Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1042/bj20111837
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol EGCG induces lipid-raft clustering and apoptotic cell death by activating protein kinase Cδ and acid sphingomyelinase through a 67 kDa laminin receptor in multiple myeloma cells

Abstract: EGCG [(−)-epigallocatechin-3-O-gallate], the major polyphenol of green tea, has cancer chemopreventive and chemotherapeutic activities. EGCG selectively inhibits cell growth and induces apoptosis in cancer cells without adversely affecting normal cells; however, the underlying molecular mechanism in vivo is unclear. In the present study, we show that EGCG-induced apoptotic activity is attributed to a lipid-raft clustering mediated through 67LR (67 kDa laminin receptor) that is significantly elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 48 publications
6
94
0
Order By: Relevance
“…However, whether ASM influences cholesterol-rich lipid raft formation, which is associated with receptor tyrosine kinase (RTK) activation (18), is unknown. We have previously reported the mechanisms by which protein kinase C (PKC) delta and ASM mediate EGCG-induced cell death via 67LR (19). However, whether 67LR/ASM signaling is involved in the inhibition of RTK activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether ASM influences cholesterol-rich lipid raft formation, which is associated with receptor tyrosine kinase (RTK) activation (18), is unknown. We have previously reported the mechanisms by which protein kinase C (PKC) delta and ASM mediate EGCG-induced cell death via 67LR (19). However, whether 67LR/ASM signaling is involved in the inhibition of RTK activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These green tea catechins (particularly EGCG) were reported to induce apoptosis and cell cycle arrest in cancer cells (Sang et al, 2005). However, some epidemiological studies have reported the null association between green tea drinking and CRC risk (Nagano et al, 2001;Sun et al, 2007;Umeda et al, 2008;Tsukamoto et al, 2012). The inconsistent results from studies based on different populations indicated that the genetic factors may involve in the protective effect of tea drinking on CRC susceptibility.…”
Section: Discussionmentioning
confidence: 70%
“…For example, how does EGCG activate 67LR? Previous publications by the Tachibana group reported the binding of EGCG to 67LR (10) and the induction of membrane lipid raft clustering by EGCG in MM cells (16). Although the binding between EGCG and 67LR could be a specific action, alteration of cell membrane structure by EGCG may be a nonspecific event that requires a large amount of EGCG to affect all types of cells, which is unlikely to occur in vivo.…”
Section: Synergistic Action Between Egcg and Vardenafil In Inducing Amentioning
confidence: 97%